175 YÜZ KIRIKLI HASTANIN RETROSPEKTİF İNCELENMESİ - AYGIT, A. Cemal; TOP, Hüsamettin; BAŞ, Sedat (Cerrahpaşa Medical Journal, 2019)
Background and Design.- Face is commonly injured part of the body which is cosmetically important. The purpose of this study was to analyze etiology of facial fractures, age groups of patients, time of injury, locations of facial fractures, method of treatment. Results.- Total of 175 patients with facial fractures treated between January 1997 and December 2001 were retrospectively analyzed. The patients were between 4 and 78 years of age. The male: female ratio was 4:1. The most common cause of injury was traffic accidents (79 patients). The largest number of fractures was found in mandibula. The number of patients suffering facial trauma was increasing in the summer months, on holidays and at night. Conclusion.- Face is a cosmetically important anatomic region of the body. For this reason, facial fractures must be restored. Prevention of etiologies of facial fractures is also important.